Penerapan Metode Fisher Yates Shuffle Pada Game Edukasi Pendidikan Agama Islam - Ahmad Thariq; Husaini; Apriani Pattimura (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Since childhood children must be familiarized with various teachings about religion. Where in the teaching process there is a need for software that is suitable for children, namely learning software in the form of educational games. Because with the existence of educational games, learning that was originally considered troublesome, difficult, boring and tiring can be an increase in motivation for students in studying Islam besides that, the purpose of this study can provide knowledge about the basics of Islamic religious learning from an early age through educational game applications and make student learning more interesting and fun. Educational games in this system by displaying learning menu options that will be selected by the user and quiz using randomized questions. Programs needed to create this application include unity 3D which uses the C# programming language and uses additional supporting software, namely adobe photoshop CS6. For the development model using the Interactive Multimedia System of Design and Development model while for the randomized question process using the fisher yates shuffle method which consists of 40 questions but for those displayed on the quiz only 10 questions so that each question will change for each student. The results with this educational game can prevent student cheating when answering questions and can increase students' concentration and interest in learning in using educational games.